Would you Marry me? The Effects of Marriage on German Couples? Allocation of Time - AbdelRahmen El Lahga; Nicolas Moreau (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Living arrangements have undergone considerable change in recent decades. In most Western countries marriage is no longer the exclusive context of family formation. In the United States (US) for instance, the number of unmarried couples nearly doubled in the 1990s, from 3:2 million couples in 1990 to 5:5 million couples in 2000 (source: U.S. Census Bureau). Le Goff (2002) reports that in the case of French women born between 1944 and 1948, 22 percent started their first union as a cohabiting union. For the cohort 1964-1968, this applies to 81 percent. In the former Federal Republic of Germany, about 38:3 percent of the women born between 1954 and 1958 started their first union outside of a formal marriage. The figure increases to 67:9 percent for the cohort 1964 -1968 (Le Goff, 2002). These demographic trends challenge the microeconomic literature in which couples living in consensual unions are implicitly assumed to act exactly as married couples.
Keywords: 330